Personil Sekolah yang Memberi Kenyamanan untuk “Curhat” - Fauziah, Mufied; Farozin, Moh.; Astuti, Budi (Institut Agama Islam Negeri Kerinci, Indonesia, 2024)
Mental health problems in students require good support from all school personnel. However, not all students who have problems are comfortable talking to others about their problems. The purpose of this study is to describe school personnel who can make students feel comfortable to tell their story. Through this research, it is hoped that data can be obtained to serve as a basis for utilizing school personnel in providing guidance and counseling services. The study used a quantitative approach of descriptive survey type. The research sample was taken from 179 vocational school students in Yogyakarta City randomly. Data collection was conducted using an open-ended questionnaire to obtain who the school personnel were most comfortable talking to. Data analysis was done by calculating the percentage of the results of filling out the questionnaire. The results showed that the majority of students felt comfortable talking to friends, with teachers coming second and other school staff. The results of this study emphasize the chances of success of guidance and counseling services by utilizing peers, such as group-based services and peer facilitator services